Deformed Heisenberg group for a particle on noncommutative spaces via canonical group quantization and extension - Mohd Faudzi Umar (Tanjong Malim, 2020)
Deformed Heisenberg group for a particle on noncommutative spaces via canonical group quantization and extension by Mohd Faudzi Umar